Musical styles in the threshold of Independence. Considerations about the villancico El Juego del Hombre by Diego Llanos (Arequipa, 1824) - Vega Salvatierra, Zoila (2019)
The religious villancico had, at the end of the 18th century, a noticeable decline in use and importance and its progressive disappearance has been documented in the cathedrals of the Hispanic world since 1750. However, its presence in the liturgy did not cease abruptly, nor did it disappear in all places equally. It is possible to find villancicos composed as late as the first third of the 19th century and to observe in many examples a series of elements from diverse textual and musical uses and styles that were preserved and maintained in the activities of musical chapels and the taste of the audience. This gave the repertoire a sense of stability in the face of the political and social changes that took place during the Independence process. The present study addresses the case of a villancico by Diego Llanos, El Juego del Hombre that was composed in Christmas 1824 probably for the cathedral of Arequipa, Peru, (in the same month and year that the battle of Ayacucho took place), as an example of the survival of the genre and the different stylistic currents that were in vogue in the Peruvian musical chapels during the War of Independence.